Preventing violence against children at schools in resource-poor environments: Operational culture as an overarching entry point. (July 2019) - Naker, Dipak
Abstract: This paper articulates a case for prioritizing prevention of violence against children (VAC) at schools in resource poor environments of developing countries. The first section makes a broad case for why it is important to focus on schools as an entry point for preventing VAC. The second section discusses how the whole school approaches prevalent in developed nations such as Positive Behavioral Intervention Support (PBIS) can be adapted and contextualized for resource poor environments. The paper delineates between school climate and the operational culture of a school and discusses why practical approaches tend to address the latter. The final section of the paper discusses an evidence-based example of such an approach; the Good School Toolkit for preventing VAC at schools in resource poor environments. The paper concludes by articulating strategic considerations to bear in mind when designing such interventions.